Karakteristik morfologi dan sebaran tipe kawin Phytophthora capsici asal lada di Pulau Jawa - Bahru Rohmah; Bambang Hadisutrisno; Dyah Manohara; Achmadi Priyatmojo (Jurnal Fitopatologi Indonesia, 2018)
Morphology characters and mating types distribution of Phytophthora capsici from black pepper in Java IslandPepper (Piper nigrum) is one of the most important spice crops in Indonesia.  Recently its production declining due to infection of foot rot disease caused by Phytophthora capsici. This pathogen has two different mating types, namely A1 and A2, in which the presence of opposite two mating types is important for sexual reproduction and formation of oospores. The movement of pepper seedling from one area to another is highly facilitated alteration of  mating type distribution map of P. capsici. The objectives of this research were to determine the morphological characteristics and the spread of mating types of P. capsici in Java. Morphology characters of P. capsici isolates were indicated by variation in sporangial size and shape, as well as types of colony appearance. The length (l) and width (w) of sporangium were in the range of 15.1–76.2 µm and 9.8–44.8 µm, respectively; while the l/w ratio was 1.12–2.27. Mating type assay showed that A2 type was more dominantly found than A1 type. This study found two different mating types present in the same area, i.e. Regency of Pacitan (East Java) and Regency of Sleman (Special Region of Yogyakarta). The findings of this research suggested that it is required more strict control strategy on the mobilization of black pepper seedling particularly in the area where the certain mating type is not found yet so that the emergence of new more virulent genotype of pathogen can be prevented.